MOLECULAR DIAGNOSTICS IN RESPIRATORY INFECTIONS: A CRITICAL ANALYSIS OF SYNDROMIC PANELS - Mazen Abdulrahman Mohammed Alamer, Talag Mohammed H. Gafary, Rashad Ali Mohammad Refae,Khalid Mohammed Derbeshi, Ali Hassan Ali Arishi, Mohammed Yahya Jarradi Ammari, Abdulmajeed Ali Abdulqader Alaqi, Ahlam Ibrahim Hadi Sowadi, Nadia Ali Qassim Juhynah, ,; Amenah Mohammed Ahmed Bokar, Radha Mohammed Ali Makaramei, Amani Yahya E Hazmi, Waleed Abdulrahman Salem Alattas, Khalid Salem Alanazi, Sami Abdullah Alotaibi, (Chelonian Research Foundation, 2022)
Respiratory tract infections (RTIs) are now receiving significant attention in the field of public health due to their extensive prevalence and the alarming rates of illness and death they cause globally. The clinical spectrum varies from those showing no symptoms or experiencing moderate infection to those with severe or life-threatening illness. Swiftness is essential in diagnostics to provide timely and effective treatment of patients. The current methodology for diagnosing respiratory tract infections (RTIs) utilizes a combination of different approaches. This includes the widely accepted conventional methods, which are considered the gold standard. Among these methods, classic culture is the most often used. Additionally, novel techniques such as molecular methods are utilized, mostly for detecting viruses and atypical bacteria. Utilizing molecular approaches with syndromic panels has the potential to serve as a very effective tool for making decisions on patient care, while it is crucial to ensure optimal use of the test in various patient groups. Their use significantly decreases the time it takes to get findings and enhances the identification of medically significant infections in comparison to traditional techniques. Furthermore, when used judiciously and evaluated with caution, syndromic panels have the potential to enhance the utilization of antimicrobials and improve patient outcomes, while also optimizing the workflow in laboratories. This review provides a comprehensive summary of the primary causes, clinical manifestations, and epidemiological characteristics of respiratory tract infections (RTIs), with a specific emphasis on laboratory diagnosis and the capabilities of syndromic panels. Keywords: respiratory tract infections, panels for syndromic diagnosis, algorithm for diagnostics, laboratory detection.